The Relationship between Stress Levels in Pregnant Women and Premature Birth at Obi South Halmahera Hospital - Ajalia Umar Bakker; Widia Shofa Ilmiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Globally, preterm childbirth is the main cause of the increase in the number of illnesses and deaths in the perinatal period. The occurrence of premature birth is triggered by various factors, one of which is the psychological stress experienced by the mother during pregnancy. This study aims to determine the relationship between the level of stress in pregnant women and the chance of premature delivery. This observational study with a cross-sectional design involved one hundred women pregnant in the third trimester at Obi Halmahera hospital. Stress levels were measured using the Perceived Stress Scale (PSS), while data related to preterm labor were obtained through medical records. The findings of the study showed a significant relationship between the level of stress of pregnant women and the risk of giving birth before the gestational age was sufficient (p<0.05). Pregnant women who experience high stress are more likely to give birth prematurely compared to those with lower stress levels. In conclusion, stress control efforts in pregnant women are an important component in antenatal services to reduce the risk of premature birth.